Globalisation and civil society in the Caribbean : integration by design or by default - Menke, Jack (2005)
Focuses on the Caribbean in the global restructuring process; conceptualization, problems and the role of civil society; and, the goals and mechanisms of integration.
A publication of the UWI-CARICOM Project